2009
DOI: 10.1111/j.1439-0272.1976.tb02139.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Functional State of Male Accessory Glands by the Analysis of Seminal Plasma*

Abstract: When one considers the secretory function of the male accessory organs of reproduction, it is important to bear in mind that some of these glandular structures, which may be regarded by morphologists as 'homologous' on the grounds of anatomical or topographical similarity, are by no means homologous in respect of their biochemical and functional characteristics. This situation is particularly true in respect of the seminal vesicle and the prostate. As a result of extensive studies it is now possible to charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In almost all mammalian species, the seminal plasma is considered as one of the main sources of the factors mediating capacitation. Seminal vesicle fluid is the major component of seminal plasma and contains many factors: the activators of sperm motility; fructose and citric acid, which act as the main energy sources of the spermatozoa; prostaglandins that suppress the female immune response; and a semen-coagulating factor that saves sperm metabolism [45][46][47][48][49]. Peitz and OldsClarke reported that the removal of the seminal vesicle in the house mouse decreased the pregnancy ratio and delayed the time of birth [50].…”
Section: Capacitation and Decapacitationmentioning
confidence: 99%
“…In almost all mammalian species, the seminal plasma is considered as one of the main sources of the factors mediating capacitation. Seminal vesicle fluid is the major component of seminal plasma and contains many factors: the activators of sperm motility; fructose and citric acid, which act as the main energy sources of the spermatozoa; prostaglandins that suppress the female immune response; and a semen-coagulating factor that saves sperm metabolism [45][46][47][48][49]. Peitz and OldsClarke reported that the removal of the seminal vesicle in the house mouse decreased the pregnancy ratio and delayed the time of birth [50].…”
Section: Capacitation and Decapacitationmentioning
confidence: 99%
“…Seminal plasma is a complex fluid that is formed mainly by organic and inorganic compounds, such as amino acids, fatty acids, ions, carbohydrates, organic salts and proteins (Mann & Lutwak-Mann, 1976), some of which play a role in regulating sperm function (Strze_ zek et al, 2005). It is known that seminal plasma is important in maintaining sperm motility and viability (Graham, 1994;Maxwell et al, 1997) and increases the resistance of canine sperm to the damage caused by 'cold shock' (N€ othling et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In the reproductive tract, SORD is believed to be involved in energy production for spermatozoa, due to the high glucose and fructose content in semen (14). Seminal vesicles and ampuls of vas deferences are the main sources of fructose in semen (15). SORD is widely expressed in human tissues (3) and therefore it may have other tissue-specific functions besides converting sorbitol to fructose, as fructose production may not be required in every tissue in which SORD is expressed.…”
Section: Discussionmentioning
confidence: 99%